Analisis Pengendalian Kualitas Produk Cacat Part X Menggunakan Lean Six Sigma di PT XYZ - Rahmadhani, Novia; Fitriani, Risma (Universitas Indraprasta PGRI Jakarta, 2024)
In the manufacturing industry, industrial competition is increasingly competitive, to produce a product that has high quality to be an added value in XYZ company's competitive advantage, so that companies produce good quality products by meeting consumer standards and tastes for the products they produce and reduce the level of product defects by the company. This study aims to analyze defective products on Part lockwasher at PT XYZ. The research used the Six Sigma method to control product quality through 5 stages, namely define, measure, analyze, improve and control. From the results of this analysis, it was found that there were 3 types of product defects that caused the resulting defects, namely high torque values, rotating bolts, and easily detached stoppers caused by machine, human, and method factors. the results of the six sigma calculation of defective products Part lockwasher during April-December there is a six sigma level of 3.463 with an average DPMO of 24803.43, and knowing the highest level of defects is caused by high torque values. These results indicate that product defects in Part lockwasher are on average for the Indonesian industry. The proposal given in this study uses 5W + 1H as an improvement to improve product quality.